Pemasaran Digital dan Harga Tiket : Pengaruhnya terhadap Keputusan Berkunjung Konser Sounds of Downtown Surabaya dengan Customer Review sebagai pemoderasi. - Madist Yura Aritonang; Diana Juni Mulyati; Agung Pujianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to determine the influence of Digital Marketing and Ticket Prices on Visit Decisions with the Customer Review moderation variable at the Sounds of Downtown Surabaya Concert. This study uses a quantitative method with a strategy using a survey, which has a total of 100 respondents with the result of distributing an e-questionnaire using a non-probability sampling technique with incidental sampling as the method. The analysis was carried out using statistical methods used to test the direct influence and moderation between the variables. This study shows that Digital Marketing has a significant effect on Visit Decisions with a significance value of 0.000. Likewise, the Ticket Price has an effect with a significance value of 0.034. The Customer Review variable was unable to moderate the influence of Digital Marketing and Ticket Prices on Visit Decisions with significance values of 0.097 and 0.667, respectively. With this research, it can be emphasized that Digital Marketing and Ticket Prices are able to drive Visit Decisions compared to Customer Reviews. Therefore, it is highly recommended for entrepreneurs who are already running a business in the entertainment/event industri or who are just starting out to encourage the optimization of Digital Marketing and periodically review the effectiveness of Ticket Prices and pay attention to the use of Customer Reviews in practice to motivate potential consumers or potential consumers.